Hierarchy-Dependent Behaviour of Dogs in the Strange Situation Test: High-Ranking Dogs Show Less Stress and Behave Less Friendly with a Stranger in the Presence of Their Owner - Viktória Bakos; Kata Vékony; Péter Pongrácz (Animals, 2025)
Cohabiting family dogs form hierarchies, and there are rank-related differences in certain behaviours even in noncompetitive situations. For companion dogs, the main limited resource could be the owner, but this assumption needs further behavioural testing. We hypothesized that dogs’ hierarchical status within multi-dog household is associated with variations in their attachment and dependency behaviours toward their owner. We tested n = 62 cohabiting companion dogs from 31 multi-dog households. The rank score of each subject was determined with a questionnaire (DRA-Q). We used the strange situation test (SST) to assess the dogs’ attachment complex towards their owner. The results show that higher-ranking dogs showed less signs of stress in the SST when their owner was present, but they also showed fewer friendly behaviours towards the stranger. Older dogs also presented fewer stress behaviours; however, they were friendlier with the stranger. This is the first time that dogs’ hierarchy was taken into consideration regarding dog–owner attachment. We can conclude that dogs’ rank and its stability could play a crucial role in creating differences between cohabiting dogs’ attachment patterns. We propose further research into the functional analysis of these behavioural differences.